The Lebanese Bubble in Paris: Diasporic Identity and Memory in Beyrouth-sur-Seine by Sabyl Ghoussoub - Arifah Arum Candra Hayuningsih; Ari Bagus Panuntun (Journal of Language and Literature, 2026)
This article discusses how diaspora identity is reconstructed through memory in Sabyl Ghoussoub's novel Beyrouth-sur-Seine. The study examines the lived experiences of Kaïssar and Hanane, Lebanese refugees who immigrated to Paris. This research asks how everyday practices are mediated as a space for negotiating identity, rather than merely memorialising the past. Drawing on Marianne Hirsch's concept of postmemory and Homi K. Bhabha's theories of cultural hybridity and the third space, this article argues that memory in the novel acts as a generative and productive force, one that allows characters to inhabit an in-between space where Lebanese and French elements are constantly negotiated and infused with new meanings. This research applies qualitative text analysis through close reading of the novel’s narrative structure, spatial descriptions, and domestic rituals. The study finds that domestic space and cultural practices, spanning both material and affective dimensions of life, act as a micro-political space of resilience. Through these everyday acts, Kaïssar and Hanane transform the experience of exile into a generative third space, reconstructing a diasporic identity that moves beyond both nostalgia and trauma. This reading contributes to contemporary discussions on migration by foregrounding the affective and intimate labour that sustains and reconfigures diasporic identities in everyday life.